Origin of frictional scaling law in circular twist layered interfaces: Simulations and theory. (January 2023) - Yan, Weidong; Ouyang, Wengen; Liu, Ze
Abstract: Structural superlubricity based on twisted layered materials has stimulated great research interests. Recent MD simulations show that the circular twisted bilayer graphene (tBLG) presenting a size scaling of friction with strong Moiré-level oscillations. To reveal the physical origin of observed abnormal scaling, we proposed a theoretical formula and derived the analytic expression of frictional size scaling law of tBLG as F ∝ θ − 3 2 R 1 2, where θ and R are the interfacial twist angle and the radius of the flake, respectively. The predicted twist angle dependent scaling law agrees well with MD simulations and provides a rationalizing explanation for the scattered power scaling law measured in various experiments. Finally, we show clear evidence that the origin of the scaling law comes from the Moiré boundary, that is, the remaining part of the twisted layered interfaces after subtracting the internal complete Moiré supercells. Our work provides new physical insights into the friction origin of layered materials and highlights the importance of Moiré boundary in the thermodynamic models of layered materials.